Structural failure assessment system exemplified by dumbbell-shaped CFST arch. (1st June 2023) - Zheng, Kaikai; Chen, Baochun; Yang, Kangkang; Deng, Yuang; Shi, Jun; Zhou, Guangchun
Abstract: The study of structural failure law is the basis of structural safety assessment, but engineering structures present complex nonlinearities and diversity, which make it difficult to analyze the failure laws of structures. However, the failure of ductile structure is a process of quantitative cumulation to qualitative change, and this turning point is the key to structural failure analysis. Based on this view, we propose a new system for structural failure assessment, which includes the identification of mutation locations, strain data visualization, structural internal force estimation, and finite element stochastic simulation, etc. Moreover, every new method is compared and validated. Experimental data of a dumbbell CFST arch model are used throughout the paper for illustration. Finally, the time-varying failure probability of the whole structure is evaluated. In summary, this paper organically combines experiment, simulation and engineering practice to provide a new approach to structural safety analysis, structural health monitoring and structural design. Highlights: A structural failure assessment system is proposed to reveal the structural failure law. The static test of dumbbell-shaped concrete filled steel tube arch model is conducted. A new method, SDMM, is proposed to identify the failure thresholds of structure. Structural internal forces are estimated with extensive strain data by IIM method.